Pediatric Spontaneous Pneumomediastinum after a Push-Up Exercise: An Uncommon Complication of a Common Exercise - Chih-Yi Tsay; Yu-Long Chen; Chien-Sheng Chen; Po-Chen Lin; Meng-Yu Wu (MDPI AG, 2020)
Pediatric spontaneous pneumomediastinum is an uncommon condition associated with infection, trauma, or coexisting structural lung pathology. Exercise-related spontaneous subcutaneous emphysema and pneumomediastinum are rarely reported. However, severe pneumomediastinum may coexist with pneumothorax, pneumorrhachis, and subcutaneous emphysema, which can potentially lead to serious complications, including airway obstruction and pneumorrhachis. Therefore, early diagnosis and timely management are important for physicians to determine the etiology and prevent further damage. Here, we present a case of exercise-related spontaneous subcutaneous emphysema and pneumomediastinum to highlight the pathogenesis and suggest therapeutic strategies.